2021
DOI: 10.1111/dsji.12232
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation for Managing Retail Inventory Flow Using RFID and Bar Code Technology

Abstract: The increasingly complex retail environment faces many inventory management challenges. Automatic identification and data capture (AIDC) technologies have been applied by retailers to address these challenges, with mixed levels of success. This article presents a classroom simulation of a retail environment in which students utilize a bar code scanner and a radio frequency identification (RFID) reader to manage inventory for the simulated retailer. From the simulation, students gain hands-on experience with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Radiofrequency identification (RFID) can help in real-time inventory control. ( Atkins et al, 2021 ) I12 Real-time tracking of SC activities using IoT Real-time tracking of SC activities became imperative during COVID-19. It helps to improve data accuracy and demand forecast, collection of data without physical interference, and up-to-the-minute inventory tracking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Radiofrequency identification (RFID) can help in real-time inventory control. ( Atkins et al, 2021 ) I12 Real-time tracking of SC activities using IoT Real-time tracking of SC activities became imperative during COVID-19. It helps to improve data accuracy and demand forecast, collection of data without physical interference, and up-to-the-minute inventory tracking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…E-procurement solutions also have the ability to integrate fraud detection and anti-counterfeiting technologies (Mackey & Cuomo 2020). Reviewed literature revealed that Auto Data Identification Creative Commons Attribution 3.0 Austria (CC BY 3.0), 2023. and Data Capture (AIDC) technologies facilitated by e-procurement systems are useful and effective in tracking pharmaceuticals throughout the supply chain (Aktins, Sener & Russo 2021;Mackey & Cuomo 2020). AIDC systems are a collection of different technologies including bar codes, radiofrequency identification (RFID), magnetic stripes and smart cards operating together in an automated way to recognize objects, collect information from them and then input them into computers, all components that lend well to procurement chain track and trace solutions (Mackey & Cuomo 2020).…”
Section: Benefits Of E-procurement In Curbing Pharmaceutical Corruptionmentioning
confidence: 99%
“…They can also establish real‐life connections and competences transferable to the work world (Morley & Jamil, 2021). Examples of recent game‐based simulations used to develop real‐world connections include managing retail inventory using RFID technology (Atkins et al., 2021) and a team‐based game for understanding behaviors related to supply shortages (Song et al., 2021). In some cases, the role of a game is not only to provide application of knowledge the students already have, but also to raise awareness and demonstrate the need for understanding effective decision‐making methodologies.…”
Section: Literature Reviewmentioning
confidence: 99%